EFEKTIVITAS PERMAINAN KOTAK KATA CERIA DALAM PENGENALAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA DINI DI TAMAN KANAKKANAK BHAKTI BUNDA PADANG - Marisa, Usnaul; Syofriend, Yul; Muryanti, Elise; Syafnita, Tisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The issue this study attempts to solve is children's low beginning reading proficiency, which is demonstrated by their inability to recognize letters, recognize symbols, and create simple words due to boring and uninteresting teaching techniques. The purpose of this study is to determine whether the "kotak kata ceria" (cheerful word box) game helps young children at Bhakti Bunda Kindergarten Padang develop their early reading abilities. This study used a pretest-posttest control group design and a quantitative technique using a quasi-experimental design. Twenty kids made up the sample, which was split into an experimental group and a control group chosen by purposive sampling. Data was collected using observation checklists, and analysis was done using homogeneity, normality, and independent sample t-tests. With the mean score rising from 16.20 to 18.20, the experimental group outperformed the control group, which only improved from 14.70 to 15.60, according to the data. The alternative hypothesis was accepted since the statistical test revealed a significant difference with a significance value of 0.005 < 0.05. These results show that the "kotak kata ceria" game is useful for improving early reading abilities, raising kids' interest, and fostering a more engaging and fun learning environment. Consequently, this game may be utilized as a cutting-edge teaching tool in early childhood education.